2018
DOI: 10.3390/sports6040130
|View full text |Cite
|
Sign up to set email alerts
|

Player Tracking Data Analytics as a Tool for Physical Performance Management in Football: A Case Study from Chelsea Football Club Academy

Abstract: Background: Global positioning system (GPS) based player movement tracking data are widely used by professional football (soccer) clubs and academies to provide insight into activity demands during training and competitive matches. However, the use of movement tracking data to inform the design of training programmes is still an open research question. Objectives: The objective of this study is to analyse player tracking data to understand activity level differences between training and match sessions, with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Price et al (2004) highlight the nature and severity of injuries that occur at academy level, and le Gall et al (2010) evaluate the fitness characteristics of young players in youth academies, highlighting which of these characteristics improve players chances of proceeding to higher levels. De Silva et al (2018) have also used the player tracking data that are available as a tool for training youth players and for physical performance management in football. They tested their work in a professional Premier League football academy.…”
Section: Training and Developing Playersmentioning
confidence: 99%
“…Price et al (2004) highlight the nature and severity of injuries that occur at academy level, and le Gall et al (2010) evaluate the fitness characteristics of young players in youth academies, highlighting which of these characteristics improve players chances of proceeding to higher levels. De Silva et al (2018) have also used the player tracking data that are available as a tool for training youth players and for physical performance management in football. They tested their work in a professional Premier League football academy.…”
Section: Training and Developing Playersmentioning
confidence: 99%
“…Our survey consisted of a set of pairs of players randomly generated by a two-step procedure, defined as follows: First, we randomly selected 35% of the players in the dataset. Second, for each selected player u, we cyclically iterated over the ranges [1,10], [11,20], and [21, ∞] and selected one value, say x, for each of these ranges, and then picked the player being x positions above u and the one being x positions below u in the role-based ranking (if they exist). This generated a set P of 211 pairs involving 202 distinct players.…”
Section: Validation Of Playerankmentioning
confidence: 99%
“…We found that c maj = 68% and c una = 74%, indicating that PlayeRank has in general a good agreement with the soccer scouts, compared to the random choice (for which c maj = c una = 50%). Figure 11 offers a more detailed view on the results of the survey by specializing c maj and c una on the three ranges of ranking differences: [1,10], [11,20], [21, ∞]. The bars show a clear and strong correlation between the concordance among scouts' evaluations (per majority or unanimity) and the difference between the positions in the ranking of the checked pairs of players: When the ranking difference is ≤10 it is c maj = 59% and c una = 61%; for larger and larger ranking differences, PlayeRank achieves a much higher concordance with experts, which is up to c maj = 86% and c una = 91% when the ranking difference is ≥20.…”
Section: Validation Of Playerankmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the study by De Silva et al [9] is the first to investigate the differences in activity demands during training and competitive matches in relation to playing positions in soccer at an elite soccer academy in order to understand differences between training and match sessions, with respect to different playing positions. The results indicate that, while there are significant position-specific differences in activity levels during matches, such differences are not observed for data pertaining to the training sessions.…”
mentioning
confidence: 99%